In-silico approaches towards the profiling of some anti-dengue virus as potent inhibitors against dengue NS-5 receptor - Samuel Ndaghiya Adawara; Gideon Adamu Shallangwa; Paul Andrew Mamza; Abdulkadir Ibrahim (Scientific African, 2021)
Flaviviruses are essential human pathogens including the dengue virus, though there is no effective antiviral drug for the treatment of the viral infections caused by these organisms currently. The NS-5 protease which is much conserved across the family of the flavivirus and necessary for viral replication represents a druggable target. The inhibition of dengue protease has been considered to be a druggable target for the treatment of dengue virus infection. The present study employed cheminformatics modeling, molecular docking analysis, and ADME (absorption, distribution, metabolism, excretion) prediction approach on some potent inhibitors of dengue viral RNA-Dependent RNA polymerase. A statistically valid quantitative structure-activity relationship (Q-SAR) model was developed. The model was validated on an independent external test set and has demonstrated statistically satisfactory performance (R2train= 0.9717, R2test = 0.80235, and cR2p= 0.8824) which proved that the built model was good, robust, reliable, and stable. Also, five molecular descriptors (MATS5c, MATS2m, GATS4c, VE1_Dzv, and ZMIC1) were shown to be meaningfully correlated with the dengue virus inhibitory activity of these compounds. The molecular docking calculations revealed the significant interactions between the amino acid residues of the active sites of the receptor with the ligands. The selected compounds (15, 28, and 29) were found to possess significant binding affinity values of -7.3, -7.7, and -8.3 kcal/mol respectively, with compound 29 having a better binding affinity better than fenretinide and S-adenosyl-L-homocysteine (SAH) with a binding affinity of -8.0 and -6.9 kcal/mol as well as low RMSD value. All the selected compounds obeyed Lipinski's rule of 5, thus entailing oral bioavailability and pharmacological activeness. The ADME predictions showed that all the selected compounds including fenretinide were inhibitors of CYP2D6 except compound 15, and non-inhibitors of CYP3A4 and cytochrome P450 enzymes with attributes of good gastrointestinal (GI) absorption, with compound 15 having excellent gastrointestinal (GI) absorption. As a consequence, the approach employed in this study and the obtained information could serve as a reliable framework to further design novel anti-dengue inhibitors.